SUSTAINABLE GOVERNANCE IN DIGITAL ART AND CREATIVE FINTECH: INTEGRATING GREEN INNOVATION WITHIN VISUAL CULTURE INDUSTRIES - Choudhari, Amey Adinath; Ranjan, Nitin; Tripathi, Diksha; Deshmukh, Prajakta B; Saxena, Jaya; Shah, Aditee Huparikar; Pise, Prakash Vishnu (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Green innovation is presented as a systematic approach to the process of integrating green into models of governance that can be used to define digital art platforms, creative markets, and FinTech-based cultural economies. Based on the sustainable governance theory, eco-digital transformation frameworks, and ethical literature in the area of FinTech, the research constructs a conceptual framework connecting environmental responsibility with transparency, accountability, and cultural value creation. The paper presents a study of the digital art- FinTech ecosystem placing emphasis on platform frameworks, assetization through NFT, tokenized forms of ownership, and the environmental impact associated therewith. It follows a mixed-method research design, which involves a qualitative policy and platform analysis and quantitative evaluation of energy consumption, the carbon intensity, and efficiency measures in case studies. The evidence shows that energy-efficient blockchain protocol, green FinTech instruments, and circular practices of digital production have an enormous impact on reducing the environmental footprint and increasing trust and economic resilience in the long term. In addition, governance systems, which tie sustainability measures to platform policies, smart-contracts and economic incentives, can be used to encourage responsible innovation without limiting artistic expression.